Budget and policy planning in devolved Kenya: a case study of citizen participation in Nairobi county - Mukorombindo, Yeukai Chido (Department of Political Studies, 2019)
The new Constitution of Kenya has devolved a significant portion of public finances, powers and responsibilities to a new sub national level of government. Kenya now has 47 Counties, each with a County assembly, an elected Governor and an administration in charge of managing public resources and providing social services. Kenyan legal frameworks such as the Public Finance Management (PFM) Act and the County Government Act (CGA) as well as specific County government participation legislation obligate County governments to facilitate and promote citizen participation in the development of County plans, budgets and policies. This thesis shall show that despite legislative efforts furthering devolution and citizen participation, the law is not always implemented and does not always function well in some instances. There appears to be little improvement in overcoming challenges faced in citizen participation of previous decentralised funds through the Local Authority Service Delivery Action Plan (LASDAP). Elite capture, resource and capacity constraints, poor bureaucratic coordination, communication as well as a limited understanding by both local officials and citizens regarding the new roles and mechanisms for participation have not resulted in simplistic 'magic bullet’ reforms. This is further compounded by a lack of information, feedback on citizen inputs and poor implementation of public participation meetings and service delivery projects. A serious limitation in terms of access, meaningfulness and inclusiveness has resulted in citizens not making use of or taking up participation opportunities. Citizens are thus opting for alternative and more effective strategies of engaging and influencing local government processes. The thesis will also show that although legislation acknowledges and provides a role for civil society to partner with government in jointly facilitating effective citizen participation in public policy; the partnership between local government and civil society does not automatically translate into effective partnerships because of poor civic capacity, unequal power dynamics, and unclear and insufficient guidelines with regards to representation.